PENGARUH KARAKTERISTIK DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP TINGKAT KONSERVATISME AKUNTANSI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2008-2010) - Wulandari, Dwinita; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2012)
This study aims to examine the influence of board of commissioner’s and audit committee characteristics for accounting conservatism level. Accounting conservatism level is a dependent variable in this study that measured by accrual measurement. Independent variable in this study are independence commissioner proportion, commissioner board size, frequency of audit committee meeting, and competence of audit committee. This research also uses control variable that is firm size. The samples of this research are the manufacturing firms listed in Indonesian Stock Exchange in 2008-2010. The samples are collected using purposive sampling method and resulted 33 firms become the samples. Data analyzed by classic assumption tests and examination hypothesis by multiple linear regression method. The result of this research show that frequency of audit committee meeting and competence of audit committee has significant effect to conservatism level measured by accrual.